Search for Spiritual Assistance in Religious Organizations: What Are the Motives of Persons Who Have Experienced Destructive Relationships at Work? - Vveinhardt, Jolita; Deikus, Mykolas (Frontiers in Psychology, 2021)
Religious assistance is an effective tool in helping the victims of violence, but so far, it has not been investigated what promotes persons aggrieved in the workplace to seek such assistance. Therefore, the purpose of this study is to identify the motives of persons who have experienced destructive relationships, which inspire the search for spiritual assistance in religious organizations, seeking to develop the provision of such service. After the analysis of the scientific literature, a questionnaire “Motives of Persons Aggrieved at Work for Seeking Spiritual Assistance (NDM-DPP-40)” was developed and validated. 463 persons working in Lithuanian organizations were surveyed using the questionnaire survey method. Correlation and regression analysis were performed. The study has shown that the victim’s religiosity is not the only condition for seeking spiritual assistance. Significant factors are congruence of values borne by the person and the religious organization, the motives arising from the relation with the person providing assistance, and motives determined by circumstances, which creates an important contextual background. The established trends show that by solving work-related problems and problems of interpersonal relationships of assistance providers, obstacles hindering the implementation of victims’ intrinsic motives to apply for spiritual assistance to the religious organization providing it can be removed. The value of the article is demonstrated by the fact that it fills the existing gaps of knowledge about motives of victims of destructive relationships at work, seeking religious-spiritual assistance. In addition, a new and reliable instrument to measure such motives is proposed.